Machine learning in classification tasks - Калайчев, Г. В. (ХНУРЕ, 2021)
The main goal of this work is to show the ways to use machine learning algorithms to solve classification tasks. One of the most efficient algorithms is Gradient Boosting (XGB Classier). This is a method which is usually used in competitions because of his speed and opportunity to work with big amount of data.
Keywords: машинне навчання; класифікація даних; Алгоритм XGBoost Classifier